An analysis of the socio-economic impact of illegal, unreported, and unregulated fishing on Somalia's coastal communities. - Jama, Luqman (School of Economics, 2025)
Illegal, unreported, and unregulated (IUU) fishing poses a significant threat to the socio-economic fabric of Somalia's coastal communities. This study employs qualitative research methods, including interviews and field observations in the districts of Eyl and Garad, to comprehensively analyze the impact of IUU fishing. Despite abundant fish stocks in Somalia's territorial waters, the fishing sector remains underdeveloped due to numerous challenges, relegating local fishermen to the margins of society. Surveys conducted on Somalia's territorial waters reveal the presence of lucrative fish stocks along its extensive coastline, making it one of the richest fishing regions in Africa. However, the IUU fishing phenomenon, with an estimated 700 international vessels operating illegally in Somali waters annually, significantly hampers the potential benefits of the fishing industry. The economic losses attributed to IUU fishing, totaling around US$300–400 million per year (AfDB, 2017), exacerbate the already underdeveloped state of the fishing sector. This research addresses the socio-economic impact of IUU fishing on two fronts: the examination of its effects on food security in the north-central coast of Somalia and the assessment of its impact on local economies and livelihoods. Interviews and field observations conducted in Eyl and Garad districts illuminate the hardships faced by local fishing communities. Participants share distressing encounters with foreign vessels engaged in IUU fishing, emphasizing the urgent need for interventions to protect the livelihoods and well-being of those dependent on maritime resources. The study underscores the complex interplay between economic challenges, food security, and the consequences of illegal fishing practices, calling for concerted efforts to mitigate the detrimental effects on Somalia's coastal communities.